If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-(-2-2z)=70
We simplify the equation to the form, which is simple to understand
7-(-2-2z)=70
Remove unnecessary parentheses
7+2+2z=70
We move all terms containing z to the left and all other terms to the right.
+2z=+70-7-2
We simplify left and right side of the equation.
+2z=+61
We divide both sides of the equation by 2 to get z.
z=30.5
| -2t^2+10+20=0 | | 5x(x-2000)-x+2000=0 | | 7x=4-(x-2) | | x-403x=2x-3-1 | | 0,3x+0,8x=12-5x | | (x/5)+10=(1/10)x | | -2+=8-2 | | 4+5x=14+4x | | 2-x=-11 | | -2(7x-2)=9(2x-2)+5 | | 3(2x-3)+2(5+1)=3x+18 | | x+5=-9x+-12 | | 4x+3x=-14 | | -4(-2)/3=x | | 5+m=11 | | 5.4-3=2.4+9 | | 14.3(2d-1)-28.6d=11.6-(d+14.2) | | 9x-58=7x-82 | | (s-12)-24=3(s+2) | | 6m=-2m+16 | | x^3-2x^2+4=0 | | 4.5*n=2.6 | | 8y-9+2y=5y-3 | | 4x^4-10x^3-55x^2-21x=0 | | (a+5)(a-5)=0 | | m^2+8m=12 | | 8x+2=2-4x | | 7x-2(x+3)=-5x-4 | | y=.88(1993) | | -0.3(0.7-0.9)=-1.83 | | 4x+3=24-8x | | -d+6=16 |